Diskriminasi Gender terhadap Tokoh Perempuan pada Novel Kelir Slindet Karya Kedung Darma Romansha (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2023)
This study aims to determine how the process of gender discrimination experienced by female charactersin the novel Kelir Slindet by Kedung Darma Romansha. This study uses the theory of genderdiscrimination. The object of research is the novel Kelir Slindet by Kedung Darma Romansha published byGramedia Pustaka Utama Book Publishers in 2014. In this study, two methods were used, namelytheoretically using an Ideological Feminist Literary Criticism approach, and methodologically using aqualitative descriptive approach. The results of the study found 4 forms of gender discriminationexperienced by female characters in this novel, namely: marginalization, stereotypes, violence, and doubleworkload. Safitri and Rukmini experience marginalization. Stereotypes are experienced by the charactersof Safitri and Saritem. Safitri and Ratini experienced violence. Saritem and Ibu Didi have a double burden.Kedung Darma Romansha tries to describe and explain how the lives of Indramayu women who work asprostitutes.